The Specifics Of The Translation Of Traditional Values In Modern Digital Information Discourse - Kommuna Umurzakova, Nilufar Farmankulova, Nodira Djabborova Munisakhon Khusaynova (International Journal of Advanced Science and Technology, 2020)
Cultural, ethnicity is “set” along with birth, the ability to speak the “native” language, the cultural environment in which it falls and which, in turn, “sets” the generally accepted standards of behavior and self-realization of the individual. Identity in the context of transculture is under intense pressure, where sustainable self-consciousness suffers, based on a sense of belonging to “one’s own” group. At the same time, the construction of a specialized identity in the electronic information format of society goes both with establishing a more significant distance with other ethnosocial groups, and with actualizing the very identity resource of the collective ethnic “I” as a kind of social “prize” in competitive linguistic policy strategies in a globalizing the world. At the same time, transcultural conflicts vividly demonstrate an example of social deviation, being a natural manifestation of the urgent contradictions in the sphere of culture, education and intercultural communication, they have a significant impact on the livelihoods and reproduction of social systems and political regimes themselves.